6,6′-Oxydichroman - Wang, Meng (International Union of Crystallography, 2007)
The title compound, C(18)H(18)O(3), was synthesized from dichroman in concentrated sulfuric acid. The molecule has a twofold axis passing through the central O atom. The dihedral angle between the two symmetry-related benzene rings is 63.6 (3)°. Weak C—H⋯π interactions are present in the structure.